A customized method to compare the projected and perceived destination images of repeat tourists. (September 2022) - Qu, Ying; Dong, Yinyin; Gao, Jing
Abstract: Research on the comparison of projected and perceived destination images has the limitation of being disconnected from the well-known concept of market segmentation. A customized host-guest image comparison method is required to develop a strategy for destinations to attract attached tourists in the marketing context. This study proposes and demonstrates the application and usefulness of a customized image comparison method for soliciting repeat tourists, considering the concepts of destination attachment and core nodes in the network. Hangzhou in China was chosen as the case study. Significant differences were identified between the core nodes of the two types of image networks. Theoretically, this study contributes to changing the research paradigm of the host-guest image contrast and customizing the marketing research of unique market segments. Managerial implications for Hangzhou and the mature destination community are also provided. Highlights: A customized image contrast method to solicit repeat tourists is provided. The implicit core nodes in the "host-guest" image networks of Hangzhou are compared. The hierarchical meanings of the image comparison results of Hangzhou are explained.